Plutarch in the religious and philosophical discourse of late antiquity - Roig Lanzillotta, Lautaro; Muñoz Gallarte, Israel (Studies in Platonism, Neoplatonism, and the Platonic tradition ;, 2012)
Either as insider or as sensitive observer, Plutarch provides us with exceptional evidence to reconstruct the spiritual and intellectual atmosphere of the first centuries CE. This collection of articles sheds important light on the religious and philosophical discourse of Late Antiquity.